The classic attributes of a profession: does recordkeeping qualify? - Pember, Margaret (RMAA, 2007)
Although records have been used and managed by man for millennia, recordkeeping is a relatively new term coined to describe the field of endeavour that encompasses the complete range of responsibilities and activities performed by those working with records regardless of type, format, age or information content. It thus encompasses both contempory records management and archives and unites records managers and archivists under one umbrella. The international standard ISO15489 supports this holistic inclusive view of recordkeeping.Technological evolution has taken recordkeeping practice from the relatively simple management of paper-based records to the highly complex management of a variety of media, in a relatively short period of time. High profile cases of fraud and business failure, and increased government regulation of both business entities and government agencies, have resulted in increased requirements for compliant recordkeeping. Such changes have necessitated a change in the knowledge base and skill levels required by recordkeeping practitioners, particularly at the more senior levels. Although some recordkeeping positions have always existed at the middle management level, these positions have increased in number, and the seniority of positions and remuneration are also increasing steadily. But, can recordkeeping be considered a profession?